Synchronisation of Weakly Coupled Oscillators - Martins, Rogério (2022)
Funding Information: This work was partially supported by the Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through the project UIDB/00297/2020 (Centro de Matemática e Aplicações). Publisher Copyright: © 2021, Springer Nature Switzerland AG.